Structural and biochemical aspects related to resistance and susceptibility of rubber tree clones to anthracnose - Magalhaes, Izabela Ponso [UNESP]; Marques, João Paulo Rodrigues; Gomes, Marcela Eloi [UNESP]; Scaloppi Junior, Erivaldo José; Fischer, Ivan Herman; Furtado, Edson Luiz [UNESP]; Henrique, Rodney Lucio Pinheiro [UNESP]; Rodrigues, Flavia Thomaz Veréchia [UNESP]; Firmino, Ana Carolina [UNESP] (MDPI, 2021)
The aim of the present study was to evaluate structural and biochemical aspects related to the interaction of resistant (RRIM 937, IAC 502 and 507) and susceptible (RRIM 600) rubber tree clones with C. tamarillo. For such analysis, ultrathin sections of the leaf limb were embedded in historesin and differently stained to verify structural alterations and presence of starch grains, arginine, lipids, tannins and lignins. The total proteins and activity of the enzymes peroxidase and (PAL) were quantified. Stomatal density was also analyzed under a scanning electron microscope. Data indicated alterations in the cell content of resistant clones inoculated with the pathogen, as well as greater lignin and lipid accumulation in these samples. For tannins, there was no difference between inoculated and non-inoculated clones. Arginine was found at greater quantities in IAC 502 and 507. Starch grains were not detected in any of the analyzed samples. Protein level and stomatal density were lower in resistant clones. Peroxidase activity was more expressive in resistant clones. PAL activity, there was no significant difference between clones. The lignin and lipids, total protein, peroxidase activity and stomatal density may be related to the resistance of rubber tree clones to anthracnose.
Keywords: Colletotrichum; Hevea brasiliensis; Lignins; Lipids; Proteins; Stomata